Liquid regionalism: A typology for regionalism in the americas - Mariano, Karina Pasquariello [UNESP]; Bressan, Regiane Nitsch; Luciano, Bruno Theodoro [UNESP] (FapUNIFESP (SciELO), 2021)
The American continent has seen the emergence of regional processes in the last 30 years, characterized by the emergence of new blocs, but also quite different projects. Faced with the new global and regional dynamics observed in the decade of 2010, this article argues that regionalism in the Americas has experienced a new wave in recent years, which we characterize as Liquid Regionalism, given the fluidity, informality and limited institutional design of the regional projects. Furthermore, the article introduces a new typology to characterize regional projects in the Americas, dividing them into platforms for consultation, cooperation and regional integration.
Keywords: Comparative Regionalism; Latin America; Regional Cooperation; Regional Integration; Regionalism; South America